Wholesale prices and price indexes. - United States. Bureau of Labor Statistics (Washington, D.C. : U.S. Dept. of Labor, Bureau of Labor Statistics, 1956)
Each issue includes also final data for preceding month.
Description based on: July 1958.
Public Affairs Information Service bulletin
Keywords: Prices -- United States -- Statistics -- Periodicals; Wholesale trade -- United States -- Statistics -- Periodicals